What do Consumers Value about Influencer Launched Brands: the Proposition of Human Brand Publics - Carlino,Francesco; Taylor,Michael (2022)
This study explored what consumers value about Influencer Launched Brands, utilising the novel concept of Human Brand Publics as a theoretical foundation to analyse this phenomenon. Simultaneously, this research aimed to develop the novel theoretical contribution of Human Brand Publics. Qualitative data from Generation Z, Influencer Launched Brands consumers was gathered and analysed to develop a deeper understanding of Influencer Launched Brands and Human Brand Publics. The theories of Human Brands’ and Brand Publics’ were integrated to introduce Human Brand Publics. Specifically, expanding on Thomson’s (2006) findings in regards to Human Brands, the findings of this study suggests that relatedness and autonomy provide value for consumers. However it also appears that the influencer should go beyond simply not suppressing competence and should instead aim to inspire competence in followers. Further, trust, authenticity and reachability all emerged as sources of value for consumers value in regards to Influenecer Launched Brands. Additionally, this study applied Arvidsson and Caliandro’s (2015) characteristics of brand publics to Influecner Launched Brands, finding that through their content the public was sustained by a focus of interest and mediation and that a multitude of individual and collective affects were aggregated, in line with brand publics. Whilst publicity was found to be a common affect, it was not deemed as significant an affect in regards to Influecner Launched Brands as proposed by Arvidsson and Caliandro. Rather, a range of affects were observed, including publicity and identity expression. This research proposes Human Brand Publics as a specific instance of Brand Publics established and revolving around a Human Brand. By aligning influencers’, Influencer Launched Brands’ and consumers’ values, and ensuring balance it appears that influencers can formulate an offering that is of significant value to consumers. This study offers numerous insights regarding consumers’ feelings towards influencers and influencer launched brands, while assessing the novel concept of Human Brand Publics.
Keywords: Influencers; Influencer Marketing; Influencer Launched Brands; Human Brands; Brand Publics; Human Brand Publics